흡연실 내 국산 담배의 입자 및 CO 오염 특징 - 김종범; 김경환; 류성희; 김민수; 정종수; 윤성택; 배귀남 (한국냄새환경학회, 2015)
It is well known that smoking generates harmful air pollutants. With smoking in buildings as well as in the streetsprohibited, the need for smoking rooms has emerged. In this study, particle and CO contamination in a 63.6 m3smoking room was experimentally investigated using Korean tobacco. Tobacco smoking was artificially simulatedusing a smoking machine. The number and size distribution of particles ranging from 10-420 nm and 0.25-32 μmwere measured using a Nanoscan (TSI model 3910) and a portable aerosol spectrometer (Grimm model 1.109),respectively. CO concentration was also monitored using an IAQ monitor (Graywolf IAQ-Xtra 610). Four tobaccoswere simultaneously smoked in each experiment, and the experiment was repeated four times. Maximum COconcentrations of 7-10 ppm were observed and high concentrations of particles (176,000-1,115,000 particles/cm3for 10-420 nm, 3,700-5,200 particles/cm3 for 0.25-32 μm) were also monitored. The dominant size of tobaccoparticles was about 100 nm in diameter.